A representação da Língua Brasileira de Sinais para os surdos no Prolibras em Roraima - Silva, Amanda Melo da (2012)
The theme of this work is focused on the representation about the Brazilian Sign Language - Libras - which perform the deaf, faced with aspects of the National Examination for Certification of Proficiency in the use and teaching of Pounds - Prolibras in Roraima. Aspects refer to the statistical data in Roraima - hearing and deaf subscribers, gifts, qualified and passed the examination. Are also related to the character of the examination, which unites proficiency testing and professional certification. In addition to the steps (practical test and objective test) and format of assessments. The main objective is to investigate the representation of sign language for deaf people in relation to the issues of Prolibras. From this key issue have developed other developments, as the discussion of identity, culture and deafness. For this research, were used as data logging, the techniques of focus group and semi-structured interviews. After recording data, the analysis was built on the perceptions of deaf people exposed on three themes that marked out this work, they are: 1) Libras, 2) proficiency, and 3) Prolibras. Reflections on the printing of the deaf participants resulted in a new perspective and perception about the sign language and splits the Prolibras: understanding the deaf experiences through the vision of subjects who perform it.